Clinicopathological studies on inclusion body hepatitis in bursectomized, thymectomized and normal chicks - Singh, Rana Dilbag; Singh, Balwant (The Indian Journal of Animal Sciences, 2012)
Clinicopathological studies on IBH was carried out in bursectomizcd and thymectomized chicks and findings were compared withnormal chicks. After bursectomy and thymectomy, chicks free from avian adeno virus detected by dot ELA method were groupedinto thymectomized, bursectomized and normal. Each group was further divided into 2 subgroups. One subgroup from each groupwas inoculated by IBH virus @ 107.5 TCID50. The other subgroup of each group was kept as control.Haematoiogical studies revealed fall of haemoglobin (Hb) and total erythrocyte count (TEC) values at 3 and 5 days post-inoculation (DPI) followed by slight increase which indicated anaemia in first stage followed by haemoconcentration due todiarrhoea. Anaemia was more severe in thymectomized infected and brusectomized infected groups. The absolute lymphocyte countas also T cell population increased considerably. Among biochemical parameters, uric acid, lactic dehydrogenase, serumglutamic oxaloacetic transaminase, serum glutamic pyruvic transaminase, alkaline phosphatase increased in all the infectedgroups as compared to the non-infected groups. The increase was more marked in thymectomized infected and bursectomizedinfected groups. Gross lesions were seen only in liver at 5 and 7 DPI which comprised enlargement, mottling and congestion.Kidneys were slightly nephrotic. Histopathologically, liver has vacuolar degeneration with congestion, haemorrhage andsometimes necrosis, intranuclear inclusion bodies in hepatocytes were seen between 5 and 7 DPI. In T1 group, thelesions were more severe and inclusions appeared 3 DPI onwards followed by BI group. Studies revealed that thymectomizedgroup was most susceptible than other groups.